Two tales of the death of God - LeDrew, Stephen (Oxford University Press, 2024)
"Across the western world, churches are emptying out and closing their doors, and more and more people are rejecting organized religion. This book addresses the causes of this decline in belief and participation in religious activities by examining two rival explanations. The first is the Enlightenment myth, which states that religious belief becomes less tenable as it is gradually replaced by a scientific worldview. This is the view promoted by a group of intellectuals known as the "new atheists" (represented most famously by evolutionary biologist Richard Dawkins), who in the early 2000s captured the imagination of young skeptics and ignited a movement for secularism by arguing that religion is the source of most of our social ills. Their view of religion as the antithesis of modern science is closely connected to ideological theories of social progress that work to justify social inequalities. After critiquing this ideological take on religion, a better alternative is presented: the sociological theory of secularization, which states that religious decline is a result of socio-economic development that has produced greater overall well-being and equality and shifting moral values that lead people to view religious ethics as a relic of a bygone era. The evidence on secularization suggests that only by working to achieve greater security and equality for all can we counter power and influence of organized religion"--